PENGARUH DIVERSIFIKASI INDUSTRI, GEOGRAFIS, DAN MEKANISME CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA - Arintasari, Okky Widya; Rohman, Abdul (Diponegoro Journal of Accounting, 2015)
The purpose of this study was to examine the influence of industrial diversification, geographic diversification,and corporate governance mechanisms toward earnings management. This research is the development of a research conducted by El Mehdi and Seboui (2011), the difference there is in addition a variable corporate governance mechanism, research samples, and measurement. Earnings management as the dependent variable measured by discretionary accruals use Modified Jones model (1995) and the independent variable are Industrial and geographic diversification are measured by the number of firms geographic and industrial segments, and corporate governance mechanisms are proxied by institusional ownership, managerial ownership, proportion of independent commissioner and audit comittee independence. This study using secondary data from annual reports and financial report. Population of this research was all companies listed in Indonesia Stock Exchange (ISX) 2011-2013. Sample of this research was all manufacturing company which listed in Indonesia Stock Exchange (ISX) 2011-2013. The study sample consisted of 47 total samples and 141 observations of the manufacturing company's financial statements. Tool the analysis in this study is multiple linear regression. Statistic program in this study used SPSS 20.The result of this research showed that institusional ownership, managerial ownership, and one control variable that is profitability have significant influence in earnings management. While, industrial and geographic diversification, proportion of independent commissioner, audit committee independence, and other control variable that is leverage have no significant influence to earning management. Implication of this research showed that industrial diversification, geographic diversification, and corporate governance mechanism have less effect on earnings management practices.